Defect-rich GaN interlayer facilitating the annihilation of threading dislocations in polar GaN crystals grown on (0001)-oriented sapphire substrates; Journal of Applied Physics; Vol. 126, iss. 8 - Barchuk M. Mykhailo; Motylenko M. V. Mykhaylo; Schneider T.; Forste M.; Roder Ch. Christian; Davydok A.; Lazarev S. V. Sergey Vladimirovich; Schimpf Ch. Christian; Wustefeld Ch. Christina; Patzold O.; Rafaja D. David (2019, 2019)
Title screen